Cloud computing adoption and perception amongst student of IIUM - Abdussalam, Salim Ahmad (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
Thanks to the rapid proliferation of internet across the world people have been able to access it easily every day. With this of course comes new services and products that will tap into this phenomenon. Such a product/service is cloud computing. Cloud computing is a technology that uses the internet as one of its basic building blocks. Since it has many uses and can be shaped in anyway, one can see why companies like Google, Microsoft and Amazon have been offering their own versions of cloud computing services. This is even evident in the types of research being conducted about cloud computing. The studies conducted deal with how businesses, people and even educational institutions can gain benefits from the use of cloud computing. Others have dealt with why students might adopt cloud computing, or even why they might switch to it. As such this study will try to discover a student's adoption and perception of cloud computing. This is what this dissertation will try to study. By using the Technology Acceptance Model (TAM) this study hoped to discover what the adoption and perception of cloud computing was amongst IIUM students. In order to better answer this problem, computer self-efficacy, perceived ease of use, perceived usefulness, behavioral intention to use and cloud computing usage were the variables used in the TAM model. The methodology used to collect and analyze the information was quantitative research methodology. It was discovered that adoption and perception of cloud computing amongst IIUM students was above average, and behavioral intention to use and perceived ease of use had the strongest effect on an IIUM students' adoption of cloud computing. The discovery made from these findings can help understand what IIUM students think of cloud computing and help IIUM find ways to use it to better the educational services they provide the students. Not only students, but staff, and the university can benefit from this study. Cloud computing is not only meant for everyday use but it can also help bring financial or resource management benefits to an educational institution.